A Biomechanical Investigation of Prominent Kinematic Factor in Drag Flick - Hussain, Ikram; Ahmad, Fuzail; Khan, Mohd. Tanveer (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2017)
Drag flick being one of the most offensive and frequently used techniques during penalty corner in field hockey requires better understanding of its complex nature in order to make the skill efficient and accurate. The aim of the present study was to determine the kinematic factors which were significantly related to ball velocity during drag flick, thereby proposing the possible suggestions to improve skill efficiency. Six male intervarsity hockey players specialist in drag flicking from Aligarh Muslim University and LNIPE, Gwalior , who’s ranged in age from 18-24 years, height ranged between 174-182 cm and weight ranged 59.4-66.8 kg were recruited for the study. The kinematic data was obtained by using two Canon Legria SF-10 camcorders. The subjects were asked to perform 15 consecutive drag flick trails from stationary ball position. Out of 15 trails best 6 successful trails were selected for each subject and were taken under consideration for analysis. Trail was defined as successful every time the ball hit the target whose dimensions were predetermined. The obtained videos data were analyzed using Max TRAQ 3D motion analysis software. The ball velocity was measured from ball-stick contact to the point of release of the ball. The factor analysis and product moment correlation statistical analysis was done using SPSSv.16. The results revealed that, left wrist velocity and acceleration, left elbow acceleration, both right and left shoulder angular velocity, left pelvic angular velocity, right knee velocity and acceleration, and left knee angular magnitude and angular velocity were significantly related with ball velocity and hence it is suggested that players should concentrate on these factors during training of the drag flick.